2015
DOI: 10.1016/j.ijscr.2015.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Right gastro-omental artery reconstruction after pancreaticoduodenectomy for subtotal esophagectomy and gastric pull-up

Abstract: HighlightsPancreaticoduodenectomy is a difficult and challenging operation, and a gastric tube is frequently used for reconstruction after subtotal esophagectomy for esophageal cancer.The right gastro-omental artery is important for supplying blood flow to the gastric tube.Surgeries for pancreatic head tumors become incredibly difficult in patients who have undergone esophageal reconstruction with a gastric tube.We describe successful arterial reconstruction using the middle colic artery in a patient who had u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…We chose MCA to reconstruct the RGEA, because we mainly use MCA to reconstruct left gastric arteries during distal pancreatectomy with celiac axis resection to preserve blood flow of the stomach, and we are experienced in the procedure [35]. Reconstruction of the RGEA using MCA has also been reported by Okochi et al [31]. ICGfluorescence imaging is helpful to confirm blood flow in the remnant stomach [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose MCA to reconstruct the RGEA, because we mainly use MCA to reconstruct left gastric arteries during distal pancreatectomy with celiac axis resection to preserve blood flow of the stomach, and we are experienced in the procedure [35]. Reconstruction of the RGEA using MCA has also been reported by Okochi et al [31]. ICGfluorescence imaging is helpful to confirm blood flow in the remnant stomach [36].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports of successful pancreaticoduodenectomy associated with esophagectomy (Table 1) [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The RGEA can be preserved in patients with non-pancreatic ductal adenocarcinoma; however, in two cases, it has been described as difficult [30,31]. Inoue et al reported radical pancreaticoduodenectomy with microvascular anastomosis of the cut end of the GDA and RGEA to secure the arterial blood flow of the gastric conduit [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 8 ] Okochi et al 2015 70 M PHC Metachoronous 5 RGEA 8m, alive RGEA, resected and reconstructed to R. branch of MCA. [ 9 ] Nagano et al 2005 55 M PVC Metachoronous 17 RCA, MCA, MCV Not described Post-DG, esophagectomy with TG. Colonic interposition.…”
Section: Discussionmentioning
confidence: 99%
“…Okochi et al [ 9 ] also reported that they successfully anastomosed the cut end of the RGEA to the right branch of the middle colic artery (MCA) microscopically after RGEA resection because the pancreatic head cancer was adjacent to the vessel.…”
Section: Discussionmentioning
confidence: 99%